1963
DOI: 10.1002/jsfa.2740140502
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of endosperm protein and aleurone cell contents from wheat, and determination of their amino‐acid composition

Abstract: The techniques of air classification, and differential centrifugation in non-aqueous media, have been combined t o isolate from flour ( a ) endosperm protein and (b) aleurone cell contents. The amino-acid composition of the isolated protein has been determined and compared with that of the total protein complex in the parent flour. The results show that in the isolated protein fraction the proportion of the glutenin/gliadin group of proteins is higher than in the parent flour. This was observed in the material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1964
1964
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Guillermlondl (8) (16,29), concentrations high enough to expect (liscrete organelles containing these constituents to he present. Figure 14 is a photograph of a portion of an aleurone grain of (iry barley fixed with osmium.…”
Section: Paleg and Hyde-electron Microscopy Ga3-treated Aleurone Dismentioning
confidence: 99%
“…Guillermlondl (8) (16,29), concentrations high enough to expect (liscrete organelles containing these constituents to he present. Figure 14 is a photograph of a portion of an aleurone grain of (iry barley fixed with osmium.…”
Section: Paleg and Hyde-electron Microscopy Ga3-treated Aleurone Dismentioning
confidence: 99%
“…Whereas the improvement of lysine reached 17.0, 25.8 and 40.3% when CB, BH and RB at optimum level 7.9, 5.2 and 9.3% were supplemented to cookies, respectively, compared with unsupplemented cookies. The biological value of the protein in germ and aleurone is higher than that of the endosperm proteins; the lysine content is 2-2.5 times as large in protein of these tissues as it is in that of endosperm [22]. In fact, most of the decrease of amino acid values in tested high dietary fibre cookies lies in the essential rather than the nonessential amino acids with a total amino acids loss of the original sample as shown in Table 1.…”
Section: Amino Acids Compositionmentioning
confidence: 95%
“…Clair (1970) This modification of a variable-density procedure described by Stevens, McDermott, and Pace (1963) utilizes mixtures of chloroform-benzene and chloroform-tetrachloroethylene instead of carbon tetrachloride-benzene, and separation is accomplished in a large beaker under normal gravity conditions instead of by centrifugation. The starting material was obtained from the medium fraction of air-classified flour and the procedure yielded quite pure preparations of aleurone bodies and relatively intact aleurone cytoplasm when examined by light microscopy ( Fig.…”
Section: (B) Amino Acid Analy8i8 Of I80lated Aleurone Bodiesmentioning
confidence: 99%
“…Protein deposits in the aleurone layer of wheat contain basic protein (Oksijuk 1961(Oksijuk , cited in 13uttrose 1963 and amino acid analyses of isolated aleurone cell contents of wheat show a marked increase in basic amino acids, especially arginine, compared to endosperm protein (Stevens, McDermott, and Pace 1963). Coates and Simmonds (1961) have also isolated protein fractions from wheat flour which have a relatively high arginine content although the studies of Graham, Morton, and Raison (1963), Jennings and Morton (1963), and Morton, Palk, and Raison (1964) have not indicated that endosperm protein bodies are rich in arginine.…”
Section: Introductionmentioning
confidence: 99%